Adipose tissue depot‐specific intracellular and extracellular cues contributing to insulin resistance in obese individuals. Issue 6 (15th April 2020) - Guzmán‐Ruiz, Rocío; Tercero‐Alcázar, Carmen; Rabanal‐Ruiz, Yoana; Díaz‐Ruiz, Alberto; El Bekay, Rajaa; Rangel‐Zuñiga, Oriol A.; Navarro‐Ruiz, M. Carmen; Molero, Laura; Membrives, Antonio; Ruiz‐Rabelo, Juan F.; Pandit, Abhay; López‐Miranda, José; et al.
Abstract: Adipose tissue dysregulation in obesity strongly influences systemic metabolic homeostasis and is often linked to insulin resistance (IR). However, the molecular mechanisms underlying adipose tissue dysfunction in obesity are not fully understood. Herein, a proteomic analysis of subcutaneous (SC) and omental (OM) fat from lean subjects and obese individuals with different degrees of insulin sensitivity was performed to identify adipose tissue biomarkers related to obesity‐associated metabolic disease. Our results suggest that dysregulation of both adipose tissue extracellular matrix (ECM) organization and intracellular trafficking processes may be associated with IR in obesity. Thus, abnormal accumulation of the small leucine‐rich proteoglycan, lumican, as observed in SC fat of IR obese individuals, modifies collagen I organization, impairs adipogenesis and activates stress processes [endoplasmic reticulum and oxidative stress] in adipocytes. In OM fat, IR is associated with increased levels of the negative regulator of the Rab family of small GTPases, GDI2, which alters lipid storage in adipocytes by inhibiting insulin‐stimulated binding of the Rab protein, Rab18, to lipid droplets. Together, these results indicate that lumican and GDI2 might play depot‐dependent, pathogenic roles in obesity‐associated IR. Our findings provide novel insights into the differential maladaptive responses of SC and OM adipose tissue linking obesity to IR.